Renal and multisystem effectiveness of 3.9 years of migalastat in a global real-world cohort: Results from the followME Fabry Pathfinders registry - Hughes, Derralynn A; Sunder-Plassmann, Gere; Jovanovic, Ana; Brand, Eva; West, Michael L; Bichet, Daniel G; Pisani, Antonio; Nowak, Albina; Torra, Roser; Khan, Aneal; Azevedo, Olga; Lehman, Anna; et al. (Journal of inherited metabolic disease, 2025)
Fabry disease is a progressive, X-linked lysosomal disorder caused by reduced or absent α-galactosidase A activity due to GLA variants. The effects of migalastat were examined in a cohort of 125 Fabry patients with migalastat-amenable GLA variants in the followME Pathfinders registry (EUPAS20599), an ongoing, prospective, patient-focused registry evaluating outcomes for current Fabry disease treatments. We report annualised estimated glomerular filtration rate (eGFR) and Fabry-associated clinical events (FACEs) in a cohort of patients who had received ≥3 years of migalastat treatment in a real-world setting. As of August 2022, 125 patients (60% male) had a mean migalastat exposure of 3.9 years. At enrolment, median age was 58 years (males, 57; females, 60) with a mean eGFR of 83.7 mL/min/1.73 m2 (n = 122; males, 83.7; females, 83.8) and a median left ventricular mass index of 115.1 g/m2 (n = 61; males, 131.2; females, 98.0). Mean (95% confidence interval) eGFR annualised rate of change in the overall cohort (n = 116) was -0.9 (-10.8, 9.9) mL/min/1.73 m2/year with a similar rate of change observed across patients with varying levels of kidney function at enrolment. Despite population age and baseline morbidity, 80% of patients did not experience a FACE during the mean 3.9 years of migalastat exposure. The incidence of renal, cardiac, and cerebrovascular events was 2.0, 83.2, and 4.1 events per 1000 patient-years, respectively. These data support a role of migalastat in preserving renal function and multisystem effectiveness during ≥3 years of migalastat treatment in this real-world Fabry population.
Keywords: výsledek terapie; 1-Deoxynojirimycin; Fabry Disease; Male; Fabry disease; kohortové studie; alpha-Galactosidase; migalastat; Glomerular Filtration Rate; Cohort Studies; 1-deoxynojirimycin; Fabryho nemoc; real world evidence; Adult; Kidney; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; registrace; Treatment Outcome; lidé; ženské pohlaví; Humans; ledviny; Registries; hodnoty glomerulární filtrace; alfa-galaktosidasa; Female; lidé středního věku; Middle Aged; prospektivní studie